Integration as a task of municipal policy. The exploration of an emerging field of local politics - Nuissl, Henning; Domann, Valentin; Engel, Susen (Raumforschung und Raumordnung | Spatial Research and Planning, 2019)
Based on three empirical case studies, this paper discusses options of addressing social integration as a task of local authorities. It furthermore aims to provide a conceptual scheme for a systematic exploration of this field of local politics. The argumentation starts from the observation that many communities in Germany have taken promising attempts to establish a genuine integration policy at the local level in the wake of recent refugee immigration. Thereby, they bolster the often-heard catchword of ’social integration occurs at particular places’ and, at the same time, support both local civil society and local economy in developing their integrative potential. However, the case studies have also shown that an ’integrative urban development’ (policy) must not refrain its efforts to the very field of integration policy but should link this policy to further cross-cutting paradigms – i.e., the principles of recognition, backstopping, and social cohesion. Examples from the case studies illustrate how to pursue local integration policies that allow for these principles. Yet, it will always be a matter of framework conditions, experiences and distinct local discourses, which of the proposed strategies, instruments or measures apply.